Embedded web server - Ahmad, Muhammad Shukri (2004)
In term of technology, internet must be the greatest thing to happen to mankind after industrial revolution. It has led us into the age of information explosion. Internet is becoming part of our everyday life through the various devices which are connected to internet at our home and work. The benefits are endless. Consider the situation where we can 'use' equipment from a remote location or work using an interactive user interface on our household device. This enables us to perform device management and even appliance diagnostics from any where in the world where you have the internet access. Thus web interfaces bring benefits to end-users as well as to manufacturers. This report discussed the design consideration of a web server based control system. Using PICDEM.net Development Board as a project, a system will be developed, allowing a user to control and monitor device remotely.